Adapting Artificial Intelligence in Pesantren: Institutional Typologies, Kyai Leadership, and Adaptive Optimism - Abidin, Muhammad Zainal; Fadlullah, M. Yusuf (Journal of Pesantren and Diniyah Studies, 2025)
This study aims to explore the integration of artificial intelligence (AI) in Islamic boarding school (pesantren) education. This study uses a literature review method. Data sources include journal articles, academic books, and official documents, such as Law No. 18 of 2019 concerning Pesantren. The results show that Islamic boarding schools have long adapted new technologies to improve the quality of education and management while maintaining their values ​​and traditions. This is evident in various aspects such as the use of online learning platforms, the use of digital Al-Qur'an and Maktabah Syamilah applications, digital information and administration systems, the use of Islamic boarding school websites and social media for promotional and da'wah purposes with interactive content to reach a wider audience, and training for Islamic students (santri) on digital literacy and AI-based edutechnopreneurship. These conditions strengthen the role of pesantren in shaping a generation that is academically competent, technologically literate, has character, has social awareness, is independent, and can face the challenges of the world of work in the new technological era. Overall, this study shows that pesantrens are able to adapt without losing their identity, values, and traditions in integrating technology. This study contributes to enriching Islamic education studies by providing a conceptual mapping of the integration of new technologies, including AI, in the context of Islamic boarding schools, an area that remains relatively underexplored.